SO040ROLE OF INTRACELLULAR CA2+ IN THE REGULATION OF THE RENAL CHLORIDE CHANNEL CLC-KA. (6th June 2020) - Gerbino, Andrea; De Zio, Roberta; Russo, Daniela; Milella, Luigi; Milano, Serena; Procino, Giuseppe; Pusch, Michael; Svelto, Maria; Carmosino, Monica
Abstract: Background and Aims: It has been recognized that the physiological role of ClC-Ka and its mouse homolog ClC-K1 in the nephron is to confer high Cl- permeability in the thin Ascending Limb of loop of Henle (tAL), which in turn is essential for establishing the high osmolarity of the renal medulla in the countercurrent system. Accordingly ClC-K1 KO mice display a severe polyuria resembling a Nephrogenic Diabetes Insipidus (NDI) phenotype. Thus, ClC-Ka in human nephron could be an interesting target for diuretic and anti-hypertensive drugs. Unfortunately the regulation of ClC-Ka in and its electrophysiological properties are still not completely known. Method: We analyzed, by whole-cell voltage-clamp, Cl - currents in HEK293 cells co-expressing GFP-ClC-Ka and the accessory m-Cherry-tagged barttin subunit, upon intracellular Ca 2+ mobilization. The patch clamp protocol consists of a holding potential from 0 mV, which is stepped to various test potentials from -195 and +125 mV for 150 ms. Pulses ended with a tail pulse to -125 mV for 20 ms. Concomitantly we monitored by live confocal microscopy, the membrane expression of either GFP-ClC-Ka or barttin-mCherry. Results: In control conditions we found a linear current/voltage relationship over a broad range of membrane voltages except of hyperpolarization below -100 mV, where the channel open probability was reduced, providing the well-known hook-shaped appearance of the I-V curve for ClC-Ka channel. Interestingly, both 100 µM ATP and 400 µg/ml of dandelion root extract (DRE), both increasing intracellular Ca 2+ in HEK293, significantly inhibited Cl - currents in a time dependent way. Pre-treatment of cells with either the Ca 2+ chelator BAPTA-AM or the PCK inhibitor Calphostin C, reverted the inhibitory effects of both ATP and DRE. Interestingly, 1µM of phorbol meristate acetate (PMA), a specific PKC activator, mimicked the inhibitory effect of ATP and DRE on Cl - currents. We finally demonstrated that 30 µM Heclin, an inhibitor of E3 ubiquitin ligase, did not revert the DRE- and ATP- induced Cl - currents inhibition, thus suggesting that the ClC-Ka inhibition is independent of channel ubiquitination. Accordingly, live confocal analysis showed that all the Ca 2+ mobilizing compounds tested did not induced neither ClC-Ka nor Barttin internalization. We hypothesized that phosphorylation in the putative PKC consensus sites present in ClC-Ka amino acidic sequence may be involved in the inhibition of channel activity. Conclusion: In conclusion, we demonstrated for the first time that the activity of ClC-Ka in renal cells could by inhibited by either receptor agonists or natural molecules able to activate an intracellular Ca 2+ /PKC pathway, thus opening venues for the development of new diuretic drugs.